A systematic review of life cycle assessments of 3D concrete printing - Arash Motalebi; Mohammad Abu Hasan Khondoker; Golam Kabir (Sustainable Operations and Computers)
The construction industry plays a crucial role in shaping our built environment, and it is imperative to adopt more sustainable and innovative practices, technologies, and tools to minimize the environmental impact. Recently, 3D printing technology has emerged as the main element of the fourth industrial revolution, Industry 4.0 which offers numerous benefits in manufacturing, including complete design freedom, savings in materials and time, enhanced efficiency, and so on. This novel technology is positively impacting various industries, including automotive, aerospace, biomedical, and now the construction industry as well. The present study aims to investigate the ecological impacts of 3D concrete printing (3DCP) by conducting a comprehensive literature review of the published articles that focused on the life cycle assessment of 3DCP-processed units. The objective was to identify current trends, areas of study that require further attention, and opportunities to lower energy consumption and environmental impacts. The literature review found that 3DCP associates with a significant reduction in global warming potential when compared to traditional construction using ordinary Portland cement-based concrete. From the life cycle analysis for 3D printed concrete performed in some articles, this review has identified opportunities to enhance the durability of 3DCP by using non-traditional materials. Additionally, improving the energy efficiency of the printing system and optimizing the structural design of printed structures can further enhance their environmental performance.